Violations of transitivity under fitness maximization - Houston, Alasdair I (The Royal Society, 2007)
We present a novel demonstration that violations of transitive choice can result from decision strategies that maximize fitness. Our results depend on how the available options, including options not currently chosen, influence a decision-maker's expectations about the future. In particular, they depend on how the presence of an option may act as an insurance against a run of bad luck in the future.